2006
DOI: 10.1606/1044-3894.3516
|View full text |Cite
|
Sign up to set email alerts
|

Hmong Immigrants’ Perceptions of Family Secrets and Recipients of Disclosure

Abstract: The purpose of this study is to examine the issues Hmong immigrants considered family secrets and to whom they would disclose their secrets when these secrets became problematic to them. Ninety-nine Hmong immigrant adults (39 males and 60 females), with ages ranging from 18 to 89 participated in this study. Content analysis found more than half of the participants considered marital issues to be secrets, while descriptive statistics found spousal arguments about family chores were the most secretive, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In addition, the patriarchal nature of Hmong culture may also contribute to a woman’s feelings of helplessness. Hmong culture, like many other Asian cultures, places a high degree of importance on face, thus marital abuse is often not discussed by the Hmong due to the stigma associated with discussing private matters with outsiders (Kaiser, 2004; Xiong, Tuicomepee, LaBlanc, & Rainey, 2006b). Therefore, Hmong clients may be reticent when discussing personal matters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patriarchal nature of Hmong culture may also contribute to a woman’s feelings of helplessness. Hmong culture, like many other Asian cultures, places a high degree of importance on face, thus marital abuse is often not discussed by the Hmong due to the stigma associated with discussing private matters with outsiders (Kaiser, 2004; Xiong, Tuicomepee, LaBlanc, & Rainey, 2006b). Therefore, Hmong clients may be reticent when discussing personal matters.…”
Section: Discussionmentioning
confidence: 99%
“…While all cultures have issues that are considered taboo, Hmong culture in particular can be very guarded around issues of sexuality. In a study about family secrets, researchers found that a high percentage of Hmong families thought that marital arguments, extramarital affairs, marital violence and abuse, delinquent children, and personal issues such as depression and financial problems should not be talked about outside of the nuclear family (Xiong, Tuicomepee, LaBlanc, & Rainey, ). This is significant because the fear of stigma and shame can make Hmong women less likely to seek professional help or utilize services for these kinds of issues, despite their significance in maintaining healthy families.…”
Section: Hmong Women As Owners Hosts and Listenersmentioning
confidence: 99%
“…Yet a worker who is unfamiliar with such norms and is not attentive to such nuances may misinterpret a client's distance in a session incorrectly (Karpel, 1980). Such issues are frequent when White practitioners assess clients of color (Xiong, Tuicomepee, LaBlanc, & Rainey, 2006).…”
Section: The Willingness Of the Client To Participatementioning
confidence: 99%
“…The fear of being a good client in the presence of someone to whom they believe they are expected to defer might influence them to say more than they are actually comfortable sharing. The gender identity of the client and the worker may influence this process as well (Ow & Katz, 1999;Xiong et al, 2006). The different combinations and the value placed on each gender may lead to more or less information being shared.…”
Section: Cultural Differencesmentioning
confidence: 99%